Concerns and challenges in flexible sigmoidoscopy screening. (August 2012) - Adebogun, Akeem O; Berg, Christine D; Laiyemo, Adeyinka O
SUMMARY  In 1992, two well-conducted case–control studies used data from two different health maintenance organizations and demonstrated a 59–79% reduction in mortality from colorectal cancer (CRC) following exposure to sigmoidoscopy. These studies highlight the possibility of reducing mortality from CRC using population-based endoscopic screening. The development of fiber optics improved the technology, and the ease of performing flexible sigmoidoscopy (FS) with widespread adoption of this screening modality. To date, FS is the only endoscopic screening modality that has been shown to reduce mortality in randomized clinical trials. This article reviews the development of sigmoidoscopy, its use in CRC screening and the current reduced role of this proven screening modality, and explores new frontiers for population-based FS screening.